Comparison of a traditional and a video game based balance training program - Kliem, A.; Wiemeyer, J. (International Journal of Computer Science in Sport, 2010)
The aim of the present study is to compare the efficiency of traditional and video game based balance training programs. 22 customers of a health care centre (age: M = 47.6 yrs; SD = 13.1) volunteered to participate in the experiment. They were randomly assigned to two experimental groups. One group underwent a traditional training program, while the other group trained using the Nintendo Wii Fit TM Balance Board. Between pre and post test procedures, training sessions were performed three times a week for three weeks. In addition to five balance tests (SEBT, ball-handling, two video games, dynamic balance), a questionnaire was applied concerning mood state, self-efficacy, physical activity enjoyment, flow and subjective experience in order to evaluate psychological effects of the interventions. Two-factor analyses of variance showed both general and differential improvements of the two groups for pre and post test measures. Both groups improved their balance performance in 4 of five tests. The traditional group showed a significantly greater improvement in two tests (SEBT: F(1,20) = 8.907, p = .007, n² = .308; ball-handling: F(1,20) = 13.578, p = .001, n² = .404), whereas the Wii group showed a significantly greater improvement in one test (Ski Slalom (F(1,20) = 5.101, p = .035, n² = .203). Psychological questionnaires revealed neither significant pre-post effects nor differences between the groups for pre and post test measurements. The results confirm that the Nintendo Wii Fit TM may be a suitable medium of training balance in prevention and rehabilitation of adults. Specific effects of training are more pronounced than transfer between virtual and real performance.